0.1T magnetic resonance image in the study of experimental hydrocephalus in rats. Accuracy of the method in the measurements of the ventricular size - Castro,Samuel Caputo de (2012)
PURPOSE: To investigate the accuracy of 1.0T Magnetic Resonance Imaging (MRI) to measure the ventricular size in experimental hydrocephalus in pup rats. METHODS: Wistar rats were subjected to hydrocephalus by intracisternal injection of 20% kaolin (n=13). Ten rats remained uninjected to be used as controls. At the endpoint of experiment animals were submitted to MRI of brain and killed. The ventricular size was assessed using three measures: ventricular ratio (VR), the cortical thickness (Cx) and the ventricles area (VA), performed on photographs of anatomical sections and MRI. RESULTS: The images obtained through MR present enough quality to show the lateral ventricular cavities but not to demonstrate the difference between the cortex and the white matter, as well as the details of the deep structures of the brain. There were no statistically differences between the measures on anatomical sections and MRI of VR and Cx (p=0.9946 and p=0.5992, respectively). There was difference between VA measured on anatomical sections and MRI (p<0.0001). CONCLUSION: The parameters obtained through 1.0T MRI were sufficient in quality to individualize the ventricular cavities and the cerebral cortex, and to calculate the ventricular ratio in hydrocephalus rats when compared to their respective anatomic slice.